2011
DOI: 10.1007/s13105-010-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Urodilatin increases renal dopamine uptake: intracellular network involved

Abstract: Dopamine and urodilatin promote natriuresis and diuresis through a common pathway that involves reversible deactivation of renal Na+, K+-ATPase. We have reported that urodilatin enhances dopamine uptake in outer renal cortex through the natriuretic peptide type A receptor. Moreover, urodilatin enhances dopamine-induced inhibition of Na+, K+-ATPase activity. The objective of the present work was to investigate the intracellular signals involved in urodilatin effects on dopamine uptake in renal cortex of kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Furthermore, in kidney, the activation/deactivation of renal Na + , K + ‐ATPase is also a final common pathway for regulation of natriuresis . For example, dopamine and urodilatin achieve their effects through a common pathway that involves deactivation of renal Na + , K + ‐ATPase, reinforcing their natriuretic and diuretic properties . The deficiency in the Na + , K + ‐ATPase activity might be a common pathogenesis of central nervous system disorders, such as central nervous system glioma, multiple sclerosis, systemic lupus erythematosis, subacute sclerosing panencephalitis, primary generalized epilepsy, PD, Down syndrome, syndrome X with multiple lacunar state, several other neurodegenerative disorders, and metabolic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in kidney, the activation/deactivation of renal Na + , K + ‐ATPase is also a final common pathway for regulation of natriuresis . For example, dopamine and urodilatin achieve their effects through a common pathway that involves deactivation of renal Na + , K + ‐ATPase, reinforcing their natriuretic and diuretic properties . The deficiency in the Na + , K + ‐ATPase activity might be a common pathogenesis of central nervous system disorders, such as central nervous system glioma, multiple sclerosis, systemic lupus erythematosis, subacute sclerosing panencephalitis, primary generalized epilepsy, PD, Down syndrome, syndrome X with multiple lacunar state, several other neurodegenerative disorders, and metabolic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we have previously reported that ANP and URO stimulate dopamine uptake by the tubular cells in the kidney through NPR-A receptors coupled to guanylate cyclase and cGMP as second messenger [20, 21]. As a physiological antagonist, Ang II exhibits the opposite effect through AT1R and PKA and cAMP as second messenger [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, administration of L-NAME reduced the natriuresis and diuresis elicited by dopamine and decreased urinary nitrate excretion, indicating NO involvement in regulation of renal sodium excretion, and, besides, NO system is required for the full expression of diuretic and natriuretic responses elicited by D1 receptor activation [62]. We have also reported that while inhibition of particulate cGMP inhibits ANP and URO stimulating effects on dopamine uptake in renal tissue, inhibition of soluble cGMP by ODQ lacked effects, suggesting that ANP and URO effects are nondependent on NO [20, 21]. Brouwers et al have reported that AT2 receptors may have a pathophysiological role in modulating renal hemodynamic effects of Ang II in SHR rats [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another member of the NP system is urodilatin (URO), which is produced by the distal kidney tubules and is considered as a local part of the natriuretic peptide system due to its diuretic effects. It was first found as a 32-amino-acid peptide in urine [29][30][31]. Altogether, each endogenous natriuretic peptide is an inseparable component of the cardiovascular system [32].…”
Section: The Natriuretic Peptide System 21 Natriuretic Peptidesmentioning
confidence: 99%